Encapsulation of sugar beet phytoglobin BvPgb 1.2 and myoglobin in a lipid sponge phase system - Gilbert, Jennifer; Christensen, Simon; Nylander, Tommy; Bülow, Leif (Frontiers in Soft Matter, 2023)
Globins are usually associated with oxygen carriage in vertebrates. However, plants also contain similar heme-containing proteins, called phytoglobins (Pgbs). Unlike conventional hemoglobin, these proteins are often linked to nitric oxide metabolism, energy metabolism and redox maintenance under hypoxic and related abiotic and biotic stress conditions. Class I and II non-symbiotic Pgbs (nsPgbs) have different degrees of heme hexacoordination. This involves direct interaction of the distal histidine in the E-helix with the sixth coordination site of the central iron, resulting in increased stability, in contrast to the oxygen storage linked to pentacoordinated globins, such as myoglobin (Mb). Due to their robustness, nsPgbs have substantial potential for various biomedical applications, particularly for iron supplementation. In this study, a class I nsPgb from sugar beet (Beta vulgaris ssp. vulgaris) was encapsulated in a lipid sponge phase system for potential protein delivery purposes and compared to a similar system of Mb containing nanoparticles. Bulk phases and dispersions were made with two lipid compositions (30/45/25 diglycerol monooleate (DGMO)/Capmul GMO-50/sorbitan monooleate (P80) and 28/42/30 DGMO/GMO-50/P80, where the DGMO/GMO-50 ratio was kept constant at 40/60). In addition, buffer effects on protein loading and particle formation were investigated. High concentrations of BvPgb1.2 (60 mg/ml) showed higher aggregation tendencies than Mb but these appeared to be transient. This property could be coupled to the higher isoelectric point (pI) of the BvPgb1.2 (7.85, compared to 6.8 for Mb), which make it more sensitive to small pH changes. In addition, excess protein/leakage was observed with Mb from the nanoparticles when analysed with size exclusion chromatography. This work highlighted the encapsulation efficiency of these proteins, which might be directly linked to difference in iron coordination and therefore, reactivity and lipid peroxidation. The interactions between the bulk phases and dispersion of the hemeproteins are complex, more research is needed to proper elucidate these relations in more detail, in order to facilitate the encapsulation capacity for heme-containing proteins in similar lipid-based systems.